Effectiveness of a STEM-Based High School Chemistry Textbook with Scaffolding Strategy to Improve Students' Critical Thinking Skills - Kadek Delita Liani; I Nyoman Suardana; Ida Bagus Putu Mardana (Postgraduate, University of Mataram, 2024)
This study aims to explain the effectiveness of STEM-based high school chemistry textbooks with scaffolding strategies to improve critical thinking skills. This type of research involved research and development by adapting the Borg and Gall development models. The research instrument used was a critical thinking essay test. The research subjects were students of class XI A SMA Negeri 3 Singaraja. The research design used was a pre-experimental with one-group pretest-posttest design. The data were analyzed using a normalized gain score and a one-sample proportion test. The results showed that the n-gain score obtained was 0.56. The one-sample proportion test results showed a significance value of 0.001. Thus, a STEM-based high school chemistry textbook with a scaffolding strategy is effective in improving students' critical thinking skills.